Off-label use in germany: a current appraisal of gynaecologic university departments - Ditsch, Nina; Kümper, C.; Summerer-Moustaki, M.; Rückert, S.; Toth, Bettina; Lenhard, M.; Strauss, M. A. (European journal of medical research, 2011)
The off-label use, referring to the applicability of pharmaceutical drugs beyond the submitted and from the Federal Institute for Drugs and Medical Devices (BfArM, Bundesamt für Arzneimittel und Medizinprodukte) certified and approved administration, is the subject of controversial discussions. the application can be considered in case of severe illness - if no therapeutic alternatives are available - or it exists as a founded perspective for achieving therapeutic success.
Gesehen am 13.06.2022